(untitled) (Journal of Nobel Medical College, 2018)
Background: The non-communicable diseases (NCDs) are one of the leading causes of death globally which accounts for 68% out of world’s 56 million deaths in 2012. Around 82% of the premature deaths due to NCDs occur in the low-and middle-income countries and 40% of global NCD-related deaths take place before the age of 70. The study aimed to assess knowledge of dietary habits and behaviour-related determinants of NCD in urban Nepalese women of Eastern Nepal. Materials and Methods: A cross-sectional study was designed by using interviewer-administered questionnaire regarding knowledge on NCD. The definitions used for the study adopted the WHO STEP wise approach to chronic disease risk factor surveillance (STEPS) survey. A total 706 women aged 20–59 years were selected randomly from Inaruwa Municipality of Eastern Nepal. Results: The overall knowledge scores was found to be 62.14% with standard deviation 14.93% and it build up that the diet- and behaviour-related causes (mean score 75.25%), diet quality (mean score 45.27%) fruit and vegetable link (mean score 30.02%), health consequences of obesity (mean score 76.82%), causes of cardiovascular disease (mean score 77.08%) and causes of certain cancers (mean score 36.10%) were calculated. The total score of knowledge regarding NCD was found to be significant with caste/ethnicity, education level, occupation, socioeconomic status, physical activity and fruit intake. Conclusions: Findings revealed the population had good overall knowledge concerning diet and nutrition related to NCD in the relatively new context of the obesity epidemic in urban set up of Nepal. However, there was poor knowledge of the benefit of eating fruit and vegetables and other preventable causes of certain cancers. Nutrition education messages need to be communicated within the general population of women. Education targeting the benefits of vegetables and fruit may have the positive impact on NCD prevention.